Cell cycle arrest and apoptosis induction by methanolic leaves extracts of four Annonaceae plants - Kitti Pumiputavon (2018)
© 2017 The Author(s). Background: Uvaria longipes (Craib) L.L.Zhou, Y.C.F.Su & R.M.K.Saunders, Artabotrys burmanicus A.DC, Marsypopetalum modestum (Pierre) B.Xue & R.M.K.Saunders and Dasymaschalon sp. have been used for traditional medicine to treat cancer-like symptoms in some ethnic groups of Thailand and Laos. Methods: We evaluated the anti-cancer activity of these Annonaceae plants against several human cancer cell lines. The apoptosis induction was detected by Annexin/propidium iodide (PI) staining. Phytochemical screening was tested by standard protocols and bioactive compounds were determined by HPLC. Results: The crude extracts from leaves of U. longipes, Dasymaschalon sp., A. burmanicus, and M. modestum showed particular effects that were found to vary depending on the cancer cell line, suggesting that the effect was in a cell-type specific manner. Interestingly, the induction of apoptotic cell death was prominent by the leaves-derived crude extract of M. modestum. This crude was, therefore, subjected to cell cycle analysis by PI staining. Results showed that this crude extract arrested cell cycle and increased the percentage of cells in the SubG1 phase in some cancer cell lines. The phytochemical screening tests indicated that all crude extracts contained tannins and flavonoids. HPLC of flavonoids using standards identified rutin as an active compound in U. longipes and Dasymaschalon sp., whereas quercetin was found in U. longipes and M. modestum. Conclusions: These crude extracts provide a new source for rutin and quercetin, which might be capable of inducing cancer cell apoptotic death in a cell-type specific manner. This suggests, by analyzing the major bioactive compounds, the potential use of these crudes for chemotherapy in the future.